Analytical reduction of a system of partial differential equations - Jurgaitis, Donatas (Lietuvos matematikos rinkinys, 1998)
A system of four of the first order partial differential equations is transformed into the system, which has blocked diagonal matrix. Under this method it is possible to split up any first order system of partial differential equations into the systems which matrices have only one eigenvalue.